FORMS AND POLITICS OF PROTECTION OF COMPETITION (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
This scientific paper will analyze the basic forms and models of competition protection from a comparative legal point of view. At the beginning of this work, the very concept of competition protection is determined, while competition is observed from different aspects, in order to define its essence and determination of its social significance.Further in the following chapters, the characteristic forms of competition protection will be discussed, which in this paper will be grouped under the general categories of direct and indirect competition protection. These two forms ensure the protection of competition through different procedures regulated by law, of which special attention will be devoted to approaches to the protection of competition in comparative law. Then, a brief overview of the most important comparative legal models of competition protection will be made and their historical genesis and basic characteristics will be presented.The scientific results of this paper and the elements of the competition protection model that is applicable in the legal systems of the countries formed on the territory of the former Yugoslavia, with a special reference to Macedonia, will be highlighted in the concluding remarks of the paper itself. (N.Vlaški, B. ,2016)
Keywords: protection of competition; direct and indirect protection of competition; American model of competition protection; European model of competition protection